Organic heterostructures obtained on ZnO/Ag/ZnO electrode. (August 2018) - Socol, M.; Preda, N.; Breazu, C.; Florica, C.; Costas, A.; Istrate, C.M.; Stanculescu, A.; Girtan, M.; Gherendi, F.
Abstract: This work is focused on the use of multilayer transparent conductive electrode (TCE) based on ZnO/Ag/ZnO in the fabrication of the organic heterostructures. The ZnO/Ag/ZnO obtained combining sputtering/thermal evaporation/sputtering techniques is featured by a good optical transmittance, a low electrical resistivity and a reduced roughness. All these characteristics recommend it as a viable alternative to indium tin oxide (ITO) for different applications. The organic materials, N, N'−diphenyl−N, N'−bis (1−naphthyl)−1, 1´−biphenyl−4, 4´−diamine (α-NPD), 5, 12-Dihydro-5-12-dimethylquino [2, 3-b]acridine-7, 14dione (DMQA) and 4, 7 diphenyl-1, 10-phenanthroline (BPhen) were deposited by vacuum thermal evaporation (VTE) method, the properties of the obtained layers being investigated by FTIR, UV-VIS and PL) spectroscopy. The I-V characteristic (recorded in dark) of the organic heterostructure fabricated on the ZnO/Ag/ZnO electrode shows diode behavior, revealing its potential applications in the organic light emitting devices (OLED). Highlights: Multilayer transparent electrode (ZnO/Ag/ZnO) was obtained by sputtering/thermal evaporation/sputtering. The optical and electrical properties of the transparent electrode are similar with those of ITO. The organic heterostructure prepared on ZnO/Ag/ZnO electrode present a typical diode behavior.